Full mouth rehabilitation of a therapy-resistant epileptic, mentally disabled person with special needs - Katinka Kesjár; Enikő Szabó; Ilona Szmirnova; Bálint Molnár; Zoltán Géczi; János Vág (Hungarian Dental Association, 2024)
The dental health of those individuals who require special dental care is way worse than the healthy population. In most cases, they need sedation or general anaesthesia during treatment and also require teamwork of a complex multidisciplinary team. These people with special needs are mostly young and have no tooth loss, so providing them with the necessary dental treatment at the right time is highly important. The patient is a 29 year old male with therapy-resistant epilepsy and mild mental retardation. First, his cooperative tendency was estimated by providing him with professional dental treatment and taking impressions. As his neurologist advised, teeth with hopeless prognoses were extracted in general anaesthesia, and also surgical coronal lengthening in the maxilla and mandible was carried out in the same way. After the conservative dental treatment process, metalceramic bridges were made using ceramic coverage only on the buccal surfaces. At the four-year control dental visit, even though he had epileptic seizures more often than before, his denture showed no signs of any damage. In the case of patients with special needs, estimating the cooperative tendency and creating the proper treatment individually is a must. In the following article, we present a complex full-mouth rehabilitation of a therapy-resistant epileptic, mentally retarded person who requires general anaesthesia for some of the treatments.